Contemporary achitecture in Gemany 1970-1996 : 50 buildings / Gerd de Bruyn ; with a preface by Wilfried Wang and an essay bay Gerd Zimmermann ; edted by Inter Nationes, Bonn in cooperation with the Geman Architecture-Museum, Frankfurt am Main - Bruyn, Gerd de
Includes index